2021
DOI: 10.1002/celc.202100491
|View full text |Cite
|
Sign up to set email alerts
|

Polyzwitterions Functionalized Nafion Barrier Toward High Performance Lithium‐Sulfur Batteries

Abstract: Lithium-sulfur (LiÀ S) batteries have emerged to be the next generation energy storage batteries due to their high theoretical capacity and low cost. Nevertheless, the growth of lithium dendrites and the notorious shuttle effects of lithium polysulfides (LiPS) during electrochemical reactions hinder the further application of LiÀ S batteries. Herein, a novel imidazolium-type polyzwitterions functionalized Nafion barrier was successfully prepared by grafting the zwitterion 3-(1-vinyl-3imidazolio) propanesulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Conceptual diagrams of the shuttle effects and Li nucleation with (e 2 ) PP and (e 3 ) ZIGLN separator for Li–S batteries. (Reproduced with permission from ref , copyright 2021, European Chemical Societies Publishing. )…”
Section: Functionalized Group-based Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual diagrams of the shuttle effects and Li nucleation with (e 2 ) PP and (e 3 ) ZIGLN separator for Li–S batteries. (Reproduced with permission from ref , copyright 2021, European Chemical Societies Publishing. )…”
Section: Functionalized Group-based Modificationsmentioning
confidence: 99%
“…As shown in Figure 17(e), Hao et al 109 grafted imidazole polyzwitterions on the surface of Nafion and coated it on PP separator, the imidazole group can anchor LiPS to inhibit the shuttle effect, and the polyzwitterions can guide the lithium ions to transfer rapidly. The resulting ZIGLN separator exhibited high ionic conductivity and demonstrated stability during cycling at high current densities.…”
Section: Modificationsmentioning
confidence: 99%
“…Naon is the brand name of a popular and commercially available sulfonated tetrauoroethylene-based uoropolymercopolymer modied to reduce polysulde shuttling in LSBs via physical and electrostatic mechanisms. [145][146][147][148][149][150] Although Naon may be used as a separator directly for its high proton conductivity and good thermal stability, 151 it is a very expensive polymer, so it is better used as a modier for polyolen separators to save material cost. Wang et al 152 modied a standard PP separator with Naon/MXene composite nanosheets via vacuum ltration.…”
Section: Common Polymersmentioning
confidence: 99%
“…Several studies demonstrated the improvement of LSB performance by exploiting Li-Nafion as a coating layer on standard polymer separators, 30 or cast over positive 31,32 or negative electrodes, 33 as a free-standing membrane 34–37 and as a constituent of the composite positive electrodes. 34 Li-Nafion is typically used in LSBs once swollen in low boiling point ether mixtures of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) to improve adhesion and reduce interfacial resistances.…”
Section: Introductionmentioning
confidence: 99%
“…29 Aer ion exchange of H + with Li + , the lithiated Naon (Li-Naon) membrane swollen with specic organic solvents possesses an ionic conductivity of 4 × 10 −4 S cm −1 at room temperature, 26 which is much larger than that of many previously reported monoionically conductive polymer electrolytes. Several studies demonstrated the improvement of LSB performance by exploiting Li-Naon as a coating layer on standard polymer separators, 30 or cast over positive 31,32 or negative electrodes, 33 as a free-standing membrane [34][35][36][37] and as a constituent of the composite positive electrodes. 34 Li-Naon is typically used in LSBs once swollen in low boiling point ether mixtures of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) to improve adhesion and reduce interfacial resistances.…”
Section: Introductionmentioning
confidence: 99%